Acromioclavicular Joint Separation: Repair Through Suture Anchors for Coracoclavicular Ligament and Nonabsorbable Suture Fixation for Acromioclavicular Joint. Issue 5 (6th September 2020) - Liu, Tao; Bao, Fei‐long; Jiang, Tao; Ji, Guang‐wei; Li, Jian‐min; Jerosch, Jörg
Abstract : Objective: To evaluate the clinical and radiographic outcomes of patients undergoing coracoclavicular (CC) ligament repair by two suture anchors and acromioclavicular (AC) joint (ACJ) fixation using heavy nonabsorbable sutures for the treatment of types III–V ACJ injuries with a minimum of 1‐year follow‐up. Methods: The clinical and radiographic outcomes of 36 consecutive patients (26 men and 10 women) who underwent anatomic reduction for acute ACJ dislocation using two suture anchors for CC ligament reconstruction and two strands of non‐absorbable stitches for ACJ fixation between December 2013 and December 2018 were reviewed. Two 3.5 mm suture anchors with double‐loaded sutures were separately inserted into the anterolateral and posteromedial portions of the coracoid process. The suture strands were passed through the hole created in the clavicle using 2.0 mm drill and tied over the clavicle. Additional ACJ augmentation using two strands of non‐absorbable heavy sutures was performed in all patients. At 3, 6, and 12 months and last follow‐up visit, the scores on the visual analog scale (VAS), the American Shoulder and Elbow Surgeons (ASES) score, Constant–Murley score, and simple shoulder test (SST) questionnaires were used to provide a final evaluation of shoulder function. Comparison between baseline and treatment results was performed. Radiographic analysis included vertical displacement and horizontal shift. Results: A total of 29 patients (20 men and nine women) were included in the study. A total of seven, six, and 16 patients had Rockwood type III, type IV, and type V ACJ dislocations, respectively. The mean patient age was 42.8 ± 13.5 years, with a mean follow‐up of 28 months (range, 12–56 months). At the 12‐month follow‐up, the mean ASES score was 92.1 ± 3.5, with a mean pain score of 0.5 ± 0.7 on the VAS and mean Constant–Murley score of 93.0 ± 2.4. The new number of positive answers on the SST was 11.5 ± 0.6. Compared with the baseline, the clinical results improved significantly ( P  < 0.05). No significant difference could be found between the 6‐ and 12‐month follow‐up evaluations ( P  > 0.05). Radiographs showed two partial loss of reduction, whereas no horizontal displacement was found in all patients. One patient developed a superficial wound infection 3 weeks postoperation. The wound healed after routine wound care. No neurovascular complications were recorded. Conclusions: CC ligament reconstruction using two suture anchors and ACJ augmentation using two strands of non‐absorbable heavy sutures on high‐grade AC dislocation is a reliable technique for restoring stability to the ACJ and can obtain good to excellent clinical results. Abstract : We describe a new technique of CC ligament reconstruction using two suture anchors and ACJ augmentation using two strands of non‐absorbable heavy sutures to restore both vertical and horizontal stability for high‐grade acromioclavicular joint dislocation.